Determining the Operating Diagram for the Cogeneration Steam Turbines. (2016) - Atănăsoae, Pavel
Abstract: Participation in the electricity market of the combined heat and power plants requires the establishment of the net and gross power of the cogeneration restriction, which will be picked from the schedule offer of power producers, to introduce it with priority in the order of merit without restrictions. The paper presents the operational regimes for the extraction condensation steam turbines and the mathematical model for determining the operating diagram. It presents concrete case for the double extraction condensation turbine type DSL-50-1. This type of turbine is found in most the combined heat and power plants of Romania, which provides centralized heat supply of the big cities.